2013
DOI: 10.1051/0004-6361/201321509
|View full text |Cite
|
Sign up to set email alerts
|

Critically-rotating accretors and non-conservative evolution in Algols

Abstract: Context. During the mass-transfer phase in Algol systems, a large amount of mass and angular momentum are accreted by the gainer star, which can be accelerated up to its critical Keplerian velocity. The fate of the gainer once it reaches this critical value is unclear. Aims. We investigate the orbital and stellar spin evolution in semi-detached binary systems, specifically for systems with rapidly rotating accretors. Our aims are to better distinguish between the different spin-down mechanisms proposed that ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 80 publications
2
58
0
1
Order By: Relevance
“…massive Algol-type systems are currently modelled Deschamps et al 2013) as undergoing initial period decrease associated with mass transfer, followed by a substantial period increase after mass ratio reversal; however, the majority of SuperWASP objects may be expected to be relatively lowmass (the survey's magnitude limits mean that it mainly detects sources in the local volume of the Milky Way, in which lower-mass stars predominate). In any case, mass-transfer evolution would not produce a symmetrical period change distribution either.…”
Section: Discussionmentioning
confidence: 99%
“…massive Algol-type systems are currently modelled Deschamps et al 2013) as undergoing initial period decrease associated with mass transfer, followed by a substantial period increase after mass ratio reversal; however, the majority of SuperWASP objects may be expected to be relatively lowmass (the survey's magnitude limits mean that it mainly detects sources in the local volume of the Milky Way, in which lower-mass stars predominate). In any case, mass-transfer evolution would not produce a symmetrical period change distribution either.…”
Section: Discussionmentioning
confidence: 99%
“…The most likely explanation is that these lines form in the wind of the hot primary and as such trace a region above the WD surface but which has to be restricted to a zone more-or-less between the two stars (as emission from an isotropic wind would present the same radial velocity variability as lines originating from the stellar surface). That the emission is restricted to a relatively small region may be indicative of a "hot spot" on the surface of the primary (Deschamps et al 2013). …”
Section: Lightcurve and Radial Velocitiesmentioning
confidence: 99%
“…Based on binary-evolution calculations with the code BINSTAR Davis et al 2013;Deschamps et al 2013), we showed that if the envelope of the He-WD progenitor is lost via tidally-enhanced winds (channel II), the circularization can be avoided. Tout & Eggleton (1988) suggested that the presence of a companion star can substantially increase the mass-loss rate of the evolved component.…”
Section: The Evolutionary Context Of Ip Erimentioning
confidence: 99%